Sports Diplomacy Research in Poland, Czechia and Slovakia. Emerging Field of Study? - Zákravský Jiří (Sciendo, 2021)
Sport is a complex phenomenon that academics across many social sciences are focusing on. The interest in sports has been observable for a long time by historians, anthropologists and sociologists. Scientists in the field of international relations are no exception. A typical way sport is studied in international relations is by paying attention to sports diplomacy. The study of sports diplomacy has become a pretty popular part of the research since the second decade of the 21st century and it is possible to observe the dominance of the authors from the American and British universities in sports diplomacy research. Based on the Web of Science dataset, at first sight, the study of sports diplomacy is not seen as a popular field of research in the Central European countries. On the other hand, this statistical measure does not describe a complex situation of what the sports diplomacy research looks like, how it is formed or how it reflects the thinking of the politicians on national public/sports diplomacy. Thus, the article aims to map sports diplomacy research in the Central European states, specifically in Poland, Czechia and Slovakia.